Penetration of charges through the surface of water - Levchenko, A.A.; Khramov, D.A.; Shikin, V.B.; Likhter, A.M.; Gryasnova, V.A. (Recent Contributions to Physics, 2015)
The general goal of this project is experimental investigation of the properties of intrinsic (electric) The general problem of this project is experimental investigation of the properties of intrinsic (electric) carriers in water and development of statistics of liquid electrolytes by analogy with semiconductor statistics. In water and development of statistics of liquid electrolytes by analogy with semiconductor statistics.